Teaching Speaking Descriptive Text Using Facebook for Senior High School Students - Fithriyah Putri Perdana; Sulistyaningsih (STKIP PGRI SIDOARJO, 2020)
The purposes of this research are to describe the implementation of the teacher in teaching speaking descriptive text using facebook for Senior High School Students, and to describe the achievement of the students in speaking using facebook. This study was descriptive qualitative research. The data were taken from the tenth grade students of senior high school in Sidoarjo. The data collecting technique used instruments of observation field note, interview and test. From the observation field note was described that the implementation of teaching learning process given were: First, the way of speaking descriptive text was explained to the students. Second, the examples of generic structure of descrptive text were displayed. Third, the way to describe picture profile from the Facebook was explained to the students. The last, the pleasant atmosphere was created while the students tried to operate Facebook for describing the profile of someone. Further, the results of test had shown that the students’ scores were good; with the average scores > 75. They show that the technique of Teaching Speaking Descriptive Text Using Facebook For Senior High School students is good for teaching speaking.